Analisis Rujukan Dan Keunikan Dalam Kitab Tafsir Tarjuman Mustafid - Lakmana, Ghairi; Nasution, Muhammad Roihan; Fitriani (Ikatan Da'i Indonesia, 2023)
This paper criticizes the views of previous researchers regarding the book Tafsir Tarjuman Mustafid by Syekh Abdurrauf As-Singkili, this book is declared not a book of interpretation and is a translation of several other books of interpretation. To set it straight, the author describes the references and uniqueness of the Tafsir Tarjuman book with samples of Surah al-Fatihah and al-Baqarah which are discussed in detail.analysis. Research on references aims to analyze the sources of quotations contained in the book and the uniqueness aims to present the character of Sheikh Abdurrauf As-Singkili's interpretation in interpreting the verses of the Koran in the Tafsir Tarjuman Mustafid book. To achieve this goal, the author uses a type of literature research with a qualitative nature and uses a library method for data collection techniques that come from primary data and secondary data. After all the data needed is collected, then use the pattern tahlili in data management then the findings are described in the form of analysis. The results of the writing show that, it is true that there were errors from previous researchers regarding their views, the author's findings can prove that it was true that as-Singkili interpreted ayat by ayat and word by word and other commentary books were only used as references, and even found many uniqueness in his interpretationsBased on the results of the writing, there are several references from al-Baiḍawi 6 times, al-Khazin 21 times, al-Jalalain 2 times and Manafi' Alquran as well as aṡ-Ṡa'labi 2 times. All references are collected as a complement to the interpretation of as-Singkili to make it easier to understand . As for the uniqueness, it is divided into two discussions, namely: a) the uniqueness of the presentation which is equipped with signs such as, interest, story, beginning, as for, the word, that is, the above and tanbih, all the signs are packed in parentheses so that they are easy to find, b) the uniqueness of the content the interpretation of as-Singkili includes special features in the explanation of surat, ayat, interpretations, ikhtilaf qiraat,asbabun nuzul, kisah and nasikh mansukh, all tend to have the same pattern and words in the beginning and end of the explanation so that it is easy to understand even by the general public.